Diversifikasi Produk Ikan untuk Solusi Peningkatan Ekonomi Kreatif Masyarakat Pesisir di Desa Sambik Elen Kabupaten Lombok Utara - Andini, Arista Suci; Darayani, Dhiafah Hera; Kamil, Muhammad Ikhsan; Hardoko, Hardoko; Bintoro, Gatut; Swandayani, Rosalina Edy; Juniawan, Alvin (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to enhance the knowledge and skills of members of the Karang Taruna youth group and local fishing groups through the application of appropriate technology in fisheries product diversification in Sambik Elen Village, North Lombok Regency. The program was implemented using a participatory approach through training in the production of fish floss and fish nuggets, as well as the use of an oil-draining spinner and product packaging techniques. Evaluation was conducted at the beginning and end of the program using pre-test and post-test instruments. The results indicate a significant improvement in partners’ knowledge and skills, reaching 92%, in processing fish catches into higher-value and longer-lasting products. The program emphasizes financial self-reliance and entrepreneurship by optimizing local potential to create sustainable flagship products, while simultaneously reducing dependence on raw fish sales and minimizing economic losses among fishermen.